Enhancement of beta-Glucosidase Activity from a Brown Rot Fungus Fomitopsis pinicola KCTC 6208 by Medium Optimization - Park, A.R., Korea Institute of Industrial Technology (KITECH), Cheonan, Republic of Korea; Park, J.H., Korea Institute of Industrial Technology (KITECH), Cheonan, Republic of Korea; Ahn, H.J., Korea Institute of Industrial Technology (KITECH), Cheonan, Republic of Korea; Jang, J.Y., Korea Institute of Industrial Technology (KITECH), Cheonan, Republic of Korea; Yu, B.J., Korea Institute of Industrial Technology (KITECH), Cheonan, Republic of Korea; Um, B.H., Hankyong National University, Anseong, Republic of Korea; Yoon, J.J., Korea Institute of Industrial Technology (KITECH), Cheonan, Republic of Korea (Mycobiology, 2015)
beta-Glucosidase, which hydrolyzes cellobiose into two glucoses, plays an important role in the process of saccharification of the lignocellulosic biomass. In this study, we optimized the activity of beta-glucosidase of brown-rot fungus Fomitopsis pinicola KCTC 6208 using the response surface methodology (RSM) with various concentrations of glucose, yeast extract and ascorbic acid, which are the most significant nutrients for activity of beta-glucosidase. The highest activity of beta-glucosidase was achieved 3.02% of glucose, 4.35% of yeast extract, and 7.41% ascorbic acid where ascorbic acid was most effective. The maximum activity of beta-glucosidase predicted by the RSM was 15.34 U/mg, which was similar to the experimental value 14.90 U/mg at the 16th day of incubation. This optimized activity of beta-glucosidase was 23.6 times higher than the preliminary activity value, 0.63 U/mg, and was also much higher than previous values reported in other fungi strains. Therefore, a simplified medium supplemented with a cheap vitamin source, such as ascorbic acid, could be a cost effective mean of increasing beta-glucosidase activity.